Husband's Support and Mother's Motivation with Exclusive Breastfeeding in Babies Aged 0–6 Months in Tipar Village, Sukabumi City - Susilawati Susilawati; Maharani Putri Anzani; Rani Fitriani Arifin (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2022)
This study aims to determine the relationship between the husband's support and motivation of mothers who have babies aged 0–6 months with exclusive breastfeeding. This type of descriptive correlational research with a cross-sectional approach uses the total sampling method with a total of 35 respondents. collecting data using a questionnaire. Data analysis using the chi-square test. The results of the study on the description of the husband's support 6 (17.14%) did not support it and 29 (82.86%) supported it. The description of the mother's motivation in breastfeeding showed the results that 15 (42.86%) had high motivation and 20 (57.14%) had low motivation. The description of giving exclusive breastfeeding at 11 (31.43%) and not giving exclusive breastfeeding at 24 (68.57%). The results of hypothesis testing showed that there was a significant relationship between the husband's support and exclusive breastfeeding with a p-value of 0.041. There is a significant relationship between the mother's motivation and exclusive breastfeeding with a p-value of 0.046. There is a relationship between a husband's support and a mother's motivation for babies aged 0–6 months with exclusive breastfeeding in Tipar Village, Sukabumi City. It is recommended that further research on the effect of breastfeeding fathers on breastfeeding success be conducted.